Combining Two Selection Principles: Sensor Arrays Based on Both Biomimetic Recognition and Chemometrics - Cuypers, Wim; Lieberzeit, Peter A. (Frontiers in Chemistry, 2018)
Electronic noses mimic smell and taste senses by using sensor arrays to assess complex samples and to detect multiple analytes simultaneously. They usually comprise sensors exhibiting broadband response behavior followed by chemometric data evaluation. However, especially for quantification of analytes it can make sense to implement receptor layers leading to increased selectivity of individual sensors in an array. Herein we report such inherently “chemoselective” sensor arrays based on biomimetic approaches. The largest part of this comparably narrow field is covered by molecularly imprinted polymers (MIP) used in both e-noses and e-tongues, e.g. to characterize headspace gas compositions, or to detect protein profiles. Other examples include applying entire cells, proteins and peptides, and aptamers, respectively, in multisensory systems. The main aim on the one hand is to increase the analytical quality of quantitative. On the other hand, such approaches target at gaining deeper understanding of olfactory processes in nature.